Proteogenomic analysis reveals RNA as a source for tumor-agnostic neoantigen identification - Tretter, Celina; Uhrig, Sebastian; Ochsenreither, Sebastian; Weichert, Wilko; Fröhling, Stefan; Rad, Roland; Hiltensperger, Michael; Krackhardt, Angela M. (Nature Communications, 2023)
Systemic pan-tumor analyses may reveal the significance of common features implicated in cancer immunogenicity and patient survival. Here, we provide a comprehensive multi-omics data set for 32 patients across 25 tumor types for proteogenomic-based discovery of neoantigens. By using an optimized computational approach, we discover a large number of tumor-specific and tumor-associated antigens. ...